Development of stereotactic radiosurgery using carbon beams (carbon-knife). (20th February 2018) - Keawsamur, Mintra; Matsumura, Akihiko; Souda, Hikaru; Kano, Yosuke; Torikoshi, Masami; Nakano, Takashi; Kanai, Tatsuaki
Abstract: The aim of this research is to develop a stereotactic-radiosurgery (SRS) technique using carbon beams to treat small intracranial lesions; we call this device the carbon knife. A 2D-scanning method is adapted to broaden a pencil beam to an appropriate size for an irradiation field. A Mitsubishi slow extraction using third order resonance through a rf acceleration system stabilized by a feed-forward scanning beam using steering magnets with a 290 MeV/u initial beam energy was used for this purpose. Ridge filters for spread-out Bragg peaks (SOBPs) with widths of 5 mm, 7.5 mm, and 10 mm were designed to include fluence-attenuation effects. The collimator, which defines field shape, was used to reduce the lateral penumbra. The lateral-penumbra width at the SOBP region was less than 2 mm for the carbon knife. The penumbras behaved almost the same when changing the air gap, but on the other hand, increasing the range-shifter thickness mostly broadened the lateral penumbra. The physical-dose rates were approximate 6 Gy s −1 and 4.5 Gy s −1 for the 10 × 10 mm 2 and 5 × 5 mm 2 collimators, respectively.